2003
DOI: 10.1063/1.1541608
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of carrier-injected DNA

Abstract: Electrical and optical characterization of DNA molecules as a function of concentration in aqueous solutionWe have studied electric properties of carrier-injected deoxyribonucleic acid ͑DNA͒ molecules. First, a current (I CA ) through a single DNA molecule was measured by the two-probe dc method with varying a distance between a cathode and an anode (d CA ). The I CA -d CA curve showed that the current rapidly decreased with increasing d CA (I CA Շ0.1 nA for d CA տ6 nm) according to a hopping model. Next, we m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
4

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 43 publications
2
26
1
4
Order By: Relevance
“…Current work is laying the foundations of elemental superconductor nanowires applications and further elucidation of the low dimensionality effect on their properties. Advances in materials and nanomaterials fabrication and characterization will certainly lead to observation of superconductivity in elements at higher temperatures, creating new opportunities for applications such as spintronics [88] or DNA integrated molecular electronics [96]. As suggested by the fast pace of discoveries in this field of superconductivity, it seems the periodic table of superconducting elements will likely need updating in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Current work is laying the foundations of elemental superconductor nanowires applications and further elucidation of the low dimensionality effect on their properties. Advances in materials and nanomaterials fabrication and characterization will certainly lead to observation of superconductivity in elements at higher temperatures, creating new opportunities for applications such as spintronics [88] or DNA integrated molecular electronics [96]. As suggested by the fast pace of discoveries in this field of superconductivity, it seems the periodic table of superconducting elements will likely need updating in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…In another attempt to resolve the puzzle around the DNA conduction properties, Watanabe et al [62] and Shigematsu et al [63]. All the three experiments demonstrated currents of order 1 nA upon application of voltage of ~1 V. The experiments by Fink et al [50] and Kasumov et al [61] showed higher currents and lower resistivities over longer molecules (hundreds of nm), but they were never reconfirmed for individual molecules.…”
Section: Single Moleculesmentioning
confidence: 99%
“…Few works have been published since 1998 describing direct electrical transport measurements conducted on single DNA molecules [12,14,33,50,[59][60][61][62][63]. In such measurements one has to bring (at least) two metal electrodes to a physical contact with a single molecule, apply voltage and measure current (or vice versa).…”
Section: Charge Transport In Device Configuration Versus Charge Transmentioning
confidence: 99%
See 1 more Smart Citation
“…We present multileveled evidence for charge transport through 26-bp-long dsDNA of a complex sequence, characterized by S-shaped current-voltage curves that show currents >220 nA at 2 V. This significant observation implies that a coherent or band transport mechanism takes over for bias potentials leading to high currents (>1 nA). molecular electronics ͉ scanning probe microscopy ͉ nanoelectronics E xperimental observations that seemed to be in dissonance raised a debate over the ability of DNA to transport charge and the nature of the conduction mechanisms through it (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). These conf licts stem from the variety of measurement approaches, sample preparations, experimental setups, and environmental conditions.…”
mentioning
confidence: 99%